Young Language Learners' motivation and attitudes : longitudinal, comparative and explanatory perspectives - Heinzmann, Sybille (Bloomsbury Academic, An imprint of Bloomsbury Publishing Plc, 2013)
Taking three different perspectives, this book looks at primary school children's language learning motivation and language attitudes. In adopting a longitudinal perspective, the book fills a research gap and provides a macro-level analysis of motivational development over time. It reveals a surprising amount of stability in primary school children's motivational and attitudinal development. The comparative perspective looks at the learners' affective dispositions with regard to English (theorized as a 'global language') and French (theorized as a 'national language'). The comparisons between.